Implementing guidelines for preventing, identifying and treating adolescent overweight and obesity—School nurses' perceptions of the challenges involved. Issue 23 (3rd July 2017) - Helseth, Sølvi; Riiser, Kirsti; Holmberg Fagerlund, Bettina; Misvær, Nina; Glavin, Kari
Abstract : Aims and objectives: To gain a better understanding of school nurses' perceptions of the challenges involved in implementing national guidelines on managing overweight and obesity in adolescents. Background: National guidelines for the management of childhood overweight and obesity are developed in many countries to translate scientific knowledge into practice. However, several challenges are involved in their implementation. Design and methods: A qualitative design with focus group interviews was chosen for data collection. Six focus group interviews with 21 school nurses were conducted. Data were analysed by qualitative content analyses. Results: National guidelines provided new directions for managing overweight and obesity in school health services. School nurses were assigned new tasks and responsibilities, which they felt they were not sufficiently prepared for, nor were they supported by extra resources. Challenges in implementation of the guidelines were identified at various levels: system level (implementation strategy, available resources, training and support, professional collaboration, referral options); individual school nurse level (perceived competence, burden of responsibility, attitudes and emotions); subject level (sensitivity of weight‐related issues); and professional level (scepticism to a body mass index cut‐off of 25 kg/m 2 as the starting point for intervention). Conclusions: School nurses felt overwhelmed in terms of implementing the guidelines. This indicates barriers not being sufficiently identified or acted upon during implementation. Further, the nurses' scepticism about the body mass index cut‐off for intervention, and their experience that measuring and follow‐up of adolescents' weight development was their responsibility alone, indicates that important discussions are needed on this as an adequate measure as well as on the professional division of responsibilities. Relevance to clinical practice: Having a proper strategy for implementation, and ensuring that necessary clinical structures and resources are available, is crucial. Including school nurses in developing and implementing such strategies is vital for success in implementing national guidelines.